The value of a law degree – part 4: a perspective from employers. Issue 2 (3rd April 2022) - Nicholson, Alex
ABSTRACT: Rising costs, an increasingly competitive graduate jobs market, and the introduction of alternative routes to highly skilled employment, have led many to question the "value" of higher education courses. This is the fourth in a series of papers which examines the value of a law degree from a range of perspectives: Part 1 explored theory from the marketing discipline in an attempt to identify the full range of possible value components; Part 2 analysed the online prospectus pages of over 50 UK law schools to understand which aspects of value were being articulated to the market; and Part 3 reported on life history interviews conducted with past and present students from a UK university, ultimately presenting a theory of value from a student viewpoint. This final paper provides a perspective from employers. It reports the findings of a qualitative study comprising 13 semi-structured interviews with people who have responsibility for trainee solicitor recruitment in England and Wales. The data reveals that whilst these influential individuals are guided by their own diverse range of value perceptions, they appear to reflect a common view that the legal profession is changing, and legal education needs to respond.